2020
DOI: 10.1096/fj.201902849r
|View full text |Cite
|
Sign up to set email alerts
|

E2F1‐Ror2 signaling mediates coordinated transcriptional regulation to promote G1/S phase transition in bFGF‐stimulated NIH/3T3 fibroblasts

Abstract: Ror2 signaling has been shown to regulate the cell cycle progression in normal and cancer cells. However, the molecular mechanism of the cell cycle progression upon activation of Ror2 signaling still remains unknown. Here, we found that the expression levels of Ror2 in G1‐arrested NIH/3T3 fibroblasts are low and are rapidly increased following the cell cycle progression induced by basic fibroblast growth factor (bFGF) stimulation. By expressing wild‐type or a dominant negative mutant of E2F1, we show that E2F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…P21 CIP1 , encoded by CDKN1A, is one of the key factors in cell cycle regulation. Several studies have pointed out that P21 CIP1 is involved in the G1-S phase cell cycle transition [30][31][32]. In our study, P21 CIP1 was predicted as a target of miR-370-3p by TargetScan.…”
Section: Discussionsupporting
confidence: 52%
“…P21 CIP1 , encoded by CDKN1A, is one of the key factors in cell cycle regulation. Several studies have pointed out that P21 CIP1 is involved in the G1-S phase cell cycle transition [30][31][32]. In our study, P21 CIP1 was predicted as a target of miR-370-3p by TargetScan.…”
Section: Discussionsupporting
confidence: 52%
“…Results of the RT‐qPCR also confirmed that DPSCs at passage twelve had much higher expression of senescence marker genes, such as p21 and p53 (Figure 1c ). A recent study had reported that the knockdown of ROR2 lead to the upregulation of cell senescence marker genes, such as p21 and the cell cycle resistance cyclin‐dependent kinase inhibitor 1B (p27) (Endo et al, 2020 ). We determined whether ROR2 and its ligand Wnt5a were involved in the senescence of DPSCs by performing cell passaging.…”
Section: Resultsmentioning
confidence: 99%
“…ROR2 is expressed in neural stem/progenitor cells (NPC) and participates in the regulation of its proliferation (Zhang et al, 2019 ). The suppressed ROR2 expression in bFGF‐stimulated NIH/3T3 cells results in an increased expression of senescence‐associated genes, such as p21 Cip1 (Endo et al, 2020 ). However, the role of ROR2 in the aging process in DPSCs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, p27 Kip1 is a cell cycle regulator first identified as a cyclin-dependent kinase antagonist [ 22 ]. It has been reported that E2F1-Ror2 signaling promotes G1/S phase transition in bFGF-stimulated NIH/3T3 fibroblasts via p27 Kip1 [ 23 ]. Additionally, Yang et al reported that pentoxifylline inhibits the progression of fibrosis by modulating FOXO1/p27 Kip1 signaling [ 24 ].…”
Section: Discussionmentioning
confidence: 99%